2018
DOI: 10.3390/ijms19040934
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Tyrosine Kinases in the Silkworm, Bombyx mori

Abstract: The tyrosine kinases (TKs) are important parts of metazoan signaling pathways and play significant roles in cell growth, development, apoptosis and disease. Genome-wide characterization of TKs has been conducted in many metazoans, however, systematic information about this family in Lepidoptera is still lacking. We retrieved 33 TK-encoding genes in silkworm and classified them into 25 subfamilies by sequence analysis, without members in AXL, FRK, PDGFR, STYK1 and TIE subfamilies. Although domain sequences in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…BmAbl1 is one of the potential targets in candidate regions. A recent report suggested that BmAbl1 had a strong correlation with cocoon shell weight [9,10]. However, how BmAbl1 affects the synthesis of silk protein is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BmAbl1 is one of the potential targets in candidate regions. A recent report suggested that BmAbl1 had a strong correlation with cocoon shell weight [9,10]. However, how BmAbl1 affects the synthesis of silk protein is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Insects 2022, 13, 967 2 of 13 Within this QTL region, the tyrosine protein kinase, BmAbl1, is considered a potential target gene affecting CSW [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the EeTK genes with the TKs of human and zebrafish, the majority of their features appear to be largely stable, including subfamily numbers and sequence characteristics. 50,51 Most metazoan genomes encode 30 TK subfamilies, although the total number of TKs representing each subfamily of orthologues varies among different lineages (Figure 4, 90 in humans, 122 in zebrafish and 114 in the electric eel). Because the conservation of gene family size across multiple species may reflect specific functional constraints, 52,53 this observation is consistent with our TK identification results in the electric eel.…”
Section: Evolutionary Relationships Within the Vertebrate Tk Repertoirementioning
confidence: 99%